Teacher Experiences with AI-based Educational Tools - Arvin, Neda; Hoseinabady, Masuod; Bayat, Bita; Zahmatkesh, Esmat (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore teachers' experiences with AI-based educational tools, focusing on their perceptions of the effectiveness of these technologies, the challenges encountered in integrating AI into teaching practices, and the support and development needed to leverage AI effectively. Utilizing a qualitative research design, this study collected data through semi-structured interviews with 20 educators from various educational levels and disciplines. Thematic analysis was employed to identify major themes and categories within the data, providing in-depth insights into the participants' experiences with AI in education. Three main themes emerged from the analysis: Perceptions of AI Effectiveness, Challenges in AI Integration, and Professional Development and Support. Within these themes, educators highlighted the pedagogical benefits of AI, including personalized learning and enhanced student engagement. However, they also reported significant challenges, such as technical issues, a lack of resources, and the need for greater teacher readiness and professional development. Ethical considerations and the need for supportive policies were also emphasized. The study concludes that while AI offers transformative potential for education, realizing this potential requires addressing significant challenges. This includes improving teacher digital literacy and readiness, ensuring equitable access to AI resources, and developing comprehensive ethical guidelines for AI use in educational settings.